Association of serum levels of inflammatory markers and adipokines with joint symptoms and structures in participants with knee osteoarthritis. (11th June 2021) - Zhu, Jimin; Ruan, Guangfeng; Cen, Han; Meng, Tao; Zheng, Shuang; Wang, Yuanyuan; Li, Baikun; Zhu, Zhaohua; Han, Weiyu; Winzenberg, Tania; Wluka, Anita E; Cicuttini, Flavia; et al.
Abstract: Objective: To investigate the longitudinal associations of serum inflammatory markers and adipokines with joint symptoms and structures in participants with knee OA. Methods: Two hundred participants (46.5% female, mean age 63.1 years, mean BMI 29.5 kg/m 2 ) from Tasmania, part of the VIDEO (Vitamin D Effect on OA) study, were randomly selected in the current study. Serum levels of 19 biomarkers, scores of WOMAC and MRI-assessed knee structures were evaluated at baseline and month 24. The patterns of biomarkers were derived from principal component analysis and their association with knee symptoms and structures were examined using adjusted generalized estimating equations. Results: Five components explained 78% of the total variance. IL-1β, -2, -4, -6, -8, -17 A, -17 F, -21, -22 and -23 loaded the highest on the first component, which was associated with increased bone marrow lesions (BMLs) and WOMAC dysfunction score. IL-10, -12 and GM-CSF loaded on the second component, which was associated with increased cartilage volume, and decreased effusion synovitis and WOMAC scores. Leptin, adipsin and CRP loaded on the third component, which was positively associated with WOMAC scores. Resistin loaded on the fourth component, which was associated with increased BMLs and cartilage defects. Apelin-36 and adiponectin loaded on the fifth component, which was associated with increased BMLs. Conclusion: Various inflammatory and metabolic components were associated differently with joint symptoms and structural changes in knee OA, suggesting a complex inflammatory and metabolic interrelationship in the pathogenesis of knee OA.